2012
DOI: 10.1002/hep.24703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Osteopontin as a Novel Marker for Early Hepatocellular Carcinoma

Abstract: This study was to identify a biomarker that could improve α-fetoprotein (AFP) performance in hepatocellular carcinoma (HCC) surveillance among patients with cirrhosis. We performed proteomic profiling of plasma from patients with cirrhosis or HCC and validated selected candidate HCC biomarkers in two geographically distinct cohorts in order to include HCC of different etiologies. Mass spectrometry profiling of highly fractionated plasma from 18 cirrhosis and 17 HCC patients identified osteopontin (OPN) as sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
234
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(256 citation statements)
references
References 23 publications
13
234
4
5
Order By: Relevance
“…In this study, OPN was demonstrated to be a potential biomarker for the detection of HCC. This finding is consistent with a previous report suggesting OPN was more sensitive than AFP as a biomarker, and was a marker of early-stage HCC [26]. In addition, up-regulated OPN has been shown to indicate a poor prognosis for HCC [27].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, OPN was demonstrated to be a potential biomarker for the detection of HCC. This finding is consistent with a previous report suggesting OPN was more sensitive than AFP as a biomarker, and was a marker of early-stage HCC [26]. In addition, up-regulated OPN has been shown to indicate a poor prognosis for HCC [27].…”
Section: Discussionsupporting
confidence: 93%
“…The same authors found that OPN levels are a potential diagnostic marker for HCC, especially among high-risk groups of patients. Shang et al (2012) monitored serum OPN levels for one year before the diagnosis of HCVrelated HCC patients. Libra et al (2005) postulated that OPN might play a role in lymphomagenesis, particularly in the context of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by previous studies, who suggested the use of OPN as a diagnostic biomarker for HCC [25,26]. Shang et al added that OPN was markedly elevated in the plasma of HCC patients, and had been identified as a diagnostic biomarker, which could also improve AFP performance in HCC surveillance among patients with HBV or HCV related cirrhosis [27].…”
Section: Results:-mentioning
confidence: 57%
“…Shang et al reported that OPN has a good sensitivity in AFP negative HCC, indicating OPN as a better marker in the early stage of HCC, so the role of OPN and AFP in HCC diagnosis is complementary [27].…”
Section: Results:-mentioning
confidence: 99%